TUANKU ABU BAKAR: TOKOH ULAMA DAN PEJUANG DARI PADANG PARIAMAN TAHUN 1942-1949 - Vatmayenti, Deswita - (Pendidikan Sejarah, 2014)
This thesis explains about a thematic biography which reviews a life journey of Tuanku Abu Bakar in certain time. The efforts of Tuanku Abu Bakar from 1942 till 1949 is demanded to be explored, because he is a historian and a religion expert who plays a role as a warrior also. The method which is done for this thesis is a historic method which is done in some parts: the first is heuristic in which the researcher collects the relevant data which is gotten from interviews, documents, and review some literatures. The second part is criticize the sources in which the researcher measures the data through external and internal critic. The third part is data analysis and data interpretation by arranging and creating the criticized data in order to be reconstructed into story form. Finally is historiography in which the writer describes the data in scientific form. Based on the result of this research, the role of Tuanku Abu Bakar as a religion expert in 1942 till 1949 when the Japanese attached our country is inviting the young to join with heiho, giving them supports, fighting the sikerei program, and taking the soldiers to to do Shalat together. The role of Tuanku abu Bakar as a religion expert in 1945 till 1949 is when holding the fight for freedom, he takes the young to do the effort to fight for the freedom, and gives support to war. Keeping the freedom is Jihad, he gives the solution for the problem, becomes the leader for praying, and gives the religious education, comprehension, and knowledge for others. The role of Tuanku Abu Bakar as a warior from 1942 till 1945 is in Japanese period like in Kuranji Hilir, Tuanku Abu Bakar as a leader for heiho community, soldiers for keeping the guns and Japanese flight area in Sintuak and keep the Japanese pos in Indarung from the attachment of Sekutu soldiers. The role of Tuanku Abu Bakar as a warior from 1945 till 1949 in freedom fight period like being the member of BKR, TKR, TRI dan TNI.